SAT0630-HPR EFFECTS OF GOLIMUMAB ON WORK PRODUCTIVITY AMONG WORK-ACTIVE ANKYLOSING SPONDYLITIS, NON-RADIOGRAPHIC AXIAL SPONDYLOARTHRITIS AND PSORIATIC ARTHRITIS PATIENTS IN GREECE: THE 'GO-UP' STUDY. (2nd June 2020) - Athanassiou, P.; Kotrotsios, A.; Kallitsakis, I.; Bounas, A.; Garyfallos, A.; Tektonidou, M.; Vosvotekas, G.; Petrikkou, E.; Katsifis, G.
Abstract : Background: Golimumab is a tumor necrosis inhibitor (TNFi) approved for the treatment of axial SpA (axSpA) and psoriatic arthritis (PsA), both falling under the Spondyloarthritis (SpA) domain. Real-world data regarding its effect on work productivity (WP) and activity impairment (AI) are limited Objectives: To assess the impact of golimumab on WP and AI over 12 months of treatment in patients with SpA, overall, and in the axSpA and PsA subpopulations Methods: A 12-month non-interventional, multicenter, prospective study performed in the routine clinical care. Data were collected at baseline (BL: prior to treatment onset), 3, 6 and 12 months. Adult work-active consented patients with axSpA [ankylosing spondylitis (AS) or non-radiographic axSpA (nr-axSpA)] or PsA, newly initiated on golimumab as per approved label, were concequetively enrolled by 20 sites. Patients prior in >1 biologic agent, or switched from another TNFi due to primary non-response or safety were excluded. WP and AI was assessed with the Work Productivity and Activity Impairment: Specific Health Problem (WPAI:SHP) instrument Results: Between Apr-2017 and May-2018, 121 (51: PsA, 70: axSpA) eligible patients (mean age: 45.4 years; 49.6% males; 69.0% overweight/obese; median disease duration: 11.3 months), (Figure 1 ), were enrolled. Median study duration participation: 11.9 months. Overall, 60.3% of the patients had previously received disease-modifying antirheumatic drugs and 16.5% biologics. At BL, the mean (standard deviation: SD) DAS28-ESR of the SpA population and PsA and axSpA subpopulations was 4.0 (1.3), 4.5 (1.2), and 3.6 (1.2), while the mean (SD) BASDAI score of patients with axSpA was 5.6 (1.9). At BL 94.1 and 96.7% of the SpA population reported WP loss and AI due to their SpA respectively, and at 3 months 87.3, and 88.0% respectively. In SpA population, the median BL WP loss and AI were 70.0% and 65.0% and decreased by a median of 31.4% and 40.0% at 3 months, by 44.2% and 40.0% at 6 months and by 50.0% and 50.0% at 12 months, respectively (Table 1 ). Improvements in WP loss and AI were noted in patients with PsA, axSpA, AS and nr-axSpA (Table 1 ). 12-month golimumab retention rate: 91.7%. No new safety signals emerged Conclusion: Patients in the SpA population and axSpA and PsA subpopulations treated with golimumab in a routine care setting experienced significant improvements in work productivity and daily activities at 3, 6 and 12 months after treatment initiation Acknowledgments: The authors thank the following investigators: Ampatziadis E., Voulgari P., Gazi S., Georgiou P., Georgountzos A., Karokis D., Mpotzoris V., Mpournazos E., Sakkas L., Sidiropoulos P., and Vassilopoulos D. The study was Sponsored by MSD, Greece. Disclosure of Interests: Panagiotis Athanassiou Grant/research support from: MSD, Genesis pharma, Janssen, Consultant of: Roche, Genesis pharma, Janssen, Speakers bureau: MSD, Janssen, Roche, Genesis pharma, Anastassios Kotrotsios Grant/research support from: MSD, Novartis, Roche, Consultant of: Bristol Myers Squibb, UCB pharma, Speakers bureau: Genesis pharma, UCB pharma, MSD, Ioannis Kallitsakis Grant/research support from: MSD, Speakers bureau: Genesis pharma, Bristol-Myers Squibb, Andreas Bounas Grant/research support from: MSD, AbbVie, Novartis, Genesis pharma, Consultant of: MSD, Bristol-Myers Squibb, UCB pharma, AbbVie, Speakers bureau: MSD, Bristol-Myers Squibb, Pfizer, Alexandros Garyfallos Grant/research support from: MSD, Aenorasis SA, Speakers bureau: MSD, Novartis, gsk, Maria Tektonidou Grant/research support from: AbbVie, MSD, Novartis and Pfizer, Consultant of: AbbVie, MSD, Novartis and Pfizer, GEORGIOS VOSVOTEKAS Grant/research support from: MSD, Janssen, Consultant of: MSD, Novartis, Roche, UCB pharma, Bristol-Myers Squibb, AbbVie, Speakers bureau: UCB pharma, Menarini, Bristol-Myers Squibb, MSD, Evangelia Petrikkou Employee of: MSD, Bristol Myers Squibb, Vianex SA, Gkikas Katsifis Grant/research support from: UCB Pharma, Janssen, Abbvie, Novartis, MSD, Aenorasis, Genesis Pharma, Pfizer, Roche, Consultant of: UCB Pharma, Janssen, Abbvie, Novartis, MSD, Aenorasis, Genesis Pharma, Pfizer, Roche, Speakers bureau: UCB Pharma, Janssen, Abbvie, Novartis, MSD, Aenorasis, Genesis Pharma, Pfizer, Roche